The FERMI free‐electron lasers. (20th April 2015) - Allaria, E.; Badano, L.; Bassanese, S.; Capotondi, F.; Castronovo, D.; Cinquegrana, P.; Danailov, M. B.; D'Auria, G.; Demidovich, A.; De Monte, R.; De Ninno, G.; Di Mitri, S.; et al.
<x xml:space="preserve">Abstract</x> FERMI is a seeded free‐electron laser (FEL) facility located at the Elettra laboratory in Trieste, Italy, and is now in user operation with its first FEL line, FEL‐1, covering the wavelength range between 100 and 20 nm. The second FEL line, FEL‐2, a high‐gain harmonic generation double‐stage cascade covering the wavelength range 20–4 nm, has also completed commissioning and the first user call has been recently opened. An overview of the typical operating modes of the facility is presented.